Hepatozoon langii n. sp. and Hepatozoon vacuolatus n. sp. (Apicomplexa: Adeleorina: Hepatozoidae) from the crag lizard (Sauria: Cordylidae) Pseudocordylus langi from the North Eastern Drakensberg escarpment, Eastern Free State, South Africa - van As, Johann; Davies, Angela J.; Smit, Nico J. (Zootaxa, 2013)
Two new haemogregarine species, Hepatozoon langii n. sp. and Hepatozoon vacuolatus n. sp., are described from the pe-ripheral blood of the high altitude crag lizard, Pseudocordylus langi, collected between October 2006 and April 2009 from the North Eastern Drakensberg, Eastern Free State. Hepatozoon langii n. sp. has maturing and mature gamonts that appear encapsulated and have narrow, curved tails. Their cytoplasm stains pinkish-purple with Giemsa, while their nuclei are pur-ple stained with stranded chromatin. Mature gamonts measure 19.1 ± 1.0 (15.4–28.1) μm long by 6.2 ± 1.1 (3.5–7.9) μm wide. Hepatozoon vacuolatus n. sp. gamonts are mostly broader at one pole than the other, have bluish-pink cytoplasm characterised by distinctive rounded and oval vacuoles, and demonstrate pink granules with Giemsa staining. Nuclei stain purple and are mainly coarsely granular. Mature gamonts measure 16.5 ± 1.0 (14.7 - 17.6) μm long by 5.9 ± 1.2 (4.0 - 7.7) μm wide. Both species parasitize erythroblasts, as well as erythrocytes and can dehaemoglobinize the cytoplasm of their host cells. Hepatozoon langii n. sp occurred in the absence of H. vacuolatus n. sp., but the latter haemogregarine always formed mixed infections with the former; no stages intermediate between the two haemogregarine types were observed.